2009
DOI: 10.5539/ijbm.v4n6p154
|View full text |Cite
|
Sign up to set email alerts
|

A Study to Determine the Effects of Customer Value on Customer Loyalty in Airline Companies Operating: Case of Turkish Air Travellers

Abstract: Enhancing customer loyalty has become a popular topic for managers, consultants, and academics. The arguments in support of loyalty are simple to understand. Loyal customers are reported to have higher customer retention rates, commit a higher share of their category spending to the firm, and are more likely to recommend others to become customers of the firm. (Reichheld, Sasser, 1990;Zeithaml, 2000, "Keiningham, et al. 2007 Traditionally, marketing activities have focused on success in the product marketplace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 16 publications
0
17
0
1
Order By: Relevance
“…Bienstock et al (2003) evaluated food safety and sanitation procedures with customer perceptions of service quality in restaurants. Atalik and Arslan (2009) determined that overall airline cabin cleanliness was important to customers. Brown et al (1991) suggested that the absence of hygiene is an important dissatisfier of the service quality experience.…”
Section: Cleanliness As a Tangible Service Quality Dimensionmentioning
confidence: 99%
“…Bienstock et al (2003) evaluated food safety and sanitation procedures with customer perceptions of service quality in restaurants. Atalik and Arslan (2009) determined that overall airline cabin cleanliness was important to customers. Brown et al (1991) suggested that the absence of hygiene is an important dissatisfier of the service quality experience.…”
Section: Cleanliness As a Tangible Service Quality Dimensionmentioning
confidence: 99%
“…Quality had a long term impact on the satisfaction of customers (Omachanu et al 2008). Atalik & Arslan (2009) found that creating value and offering quality of service offered to customer creates loyal customers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As airlines operate under market forces which demand lower airfares, they struggle to maintain customer service levels (NZTRI 2009). However it is crucial that service organisations realise that the human element plays an important role in achieving service quality and airlines can gain greater understanding and awareness of customer needs and wants through wider communication channels (Atal et al 2009).…”
Section: Baby Boomer Travellers and Customer Service/communicationmentioning
confidence: 99%